Education Intervention on Chronotherapy for Final-Year Pharmacy Students - Gagandeep Kaur; Maya Saba; Craig L. Phillips; Keith Wong; Bandana Saini (MDPI AG, 2015)
Chronotherapy involves altering the timing of medication administration in coordination with the body's circadian rhythms to improve the overall control of disease and to minimise treatment side effects. Training on chronotherapy requires students to map different topics learnt in earlier years of their professional degree and apply these concepts clinically. This requires strategic educational design. Therefore, the aim of the study was to develop, implement and evaluate an educational intervention focusing on the application of chronotherapy for final-year undergraduate pharmacy students. An educational intervention utilizing multiple learning strategies for enhancing chronotherapy related awareness was designed and implemented in the final year undergraduate pharmacy cohort at the University of Sydney Australia (2013). A custom-designed questionnaire measuring awareness about (13 items scored 0 or 1), and attitudes (12 items scored on a Likert scale of 1-5) towards chronotherapy was administered pre and post intervention to evaluate its impact. The pre-intervention mean total awareness and attitude scores were 6.5 ± 2.0 (score range 0-13) and 47.4 ± 6.9 (score range 12-60) respectively. The mean total post-intervention scores were significantly higher for total awareness (10.1 ± 1.9) and attitude (54.0 ± 6.0). Carefully designed educational interventions utilising pedagogic principles for pharmacy students can improve awareness of and enhance positive attitudes toward pharmacists' roles in optimizing drug therapy using chronotherapy.